The 9th International Conference on Computing and InformationTechnology (IC2IT2013) : 9th-10th May 2013 King Mongkut's University of Technology North Bangkok - Unger, Herwig; Boonkrong, Sirapat; Meesad, Phayung (Advances in intelligent systems and computing, 2013)
This volume contains the papers of the 9th International Conference on Computing and Information Technology (IC2IT 2013) held at King Mongkut's University of Technology North Bangkok (KMUTNB), Bangkok, Thailand, on May 9th-10th, 2013. Traditionally, the conference is organized in conjunction with the National Conference on Computing and Information Technology, one of the leading Thai national events in the area of Computer Science and Engineering. The conference as well as this volume is structured into 3 main tracks on Data Networks/Communication, Data Mining/Machine Learning, and Human Interfaces/Image processing.